2022
DOI: 10.48550/arxiv.2205.07511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tempestuous life beyond R500: X-ray view on the Coma cluster with SRG/eROSITA. II. Shock & Relic

Abstract: This is the second paper in a series of studies of the Coma cluster using the SRG/eROSITA X-ray data obtained in the course of the calibration and performance verification observations. Here we focus on the region adjacent to the radio source 1253+275 (Radio Relic, RR hereafter). We show that the X-ray surface brightness steepest gradient at ∼ 79 (∼ 2.2 Mpc ≈ R 200c ) is almost co-spatial with the outer edge of RR, with an offset of about ∼ 100−150 kpc between the derived position of the shock front and the br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…Recently from the X-ray images obtained with the SRG/ eROSITA, Churazov et al (2021Churazov et al ( , 2022 found a faint X-ray bridge connecting the NGC 4839 group with the main cluster. This bridge may be a remnant of stripped gas while NGC 4839 moves outward from the main cluster to the current position, showing that it is strong evidence that NGC 4839 already passed the main cluster core (see their Figure 11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently from the X-ray images obtained with the SRG/ eROSITA, Churazov et al (2021Churazov et al ( , 2022 found a faint X-ray bridge connecting the NGC 4839 group with the main cluster. This bridge may be a remnant of stripped gas while NGC 4839 moves outward from the main cluster to the current position, showing that it is strong evidence that NGC 4839 already passed the main cluster core (see their Figure 11).…”
Section: Discussionmentioning
confidence: 99%
“…This bridge may be a remnant of stripped gas while NGC 4839 moves outward from the main cluster to the current position, showing that it is strong evidence that NGC 4839 already passed the main cluster core (see their Figure 11). Churazov et al (2021Churazov et al ( , 2022 also pointed out that the existence of the bow shock at » ¢ R 33 (960 kpc) in the west, and the radio relic at R ≈ 2.1 Mpc in the SW (Bonafede et al 2021) may correspond, respectively, to the secondary shock (produced when crossing the apocenter) and the primary shock (produced when crossing the main cluster core) caused by the merging event with NGC 4839.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each feature can be explained with either the pre-merger scenario or the post-merger scenario. Recently the postmerger scenario, which can better explain the existence of X-ray/radio substructures (in particular, bridges and streams), appears to be more supported (Lyskova et al 2019;Churazov et al 2021Churazov et al , 2022Bonafede et al 2021). However, even in the recent discussions of both scenarios based on various observations, Healy et al (2021) state that Nevertheless, the question whether the NGC 4839 group is on its first infall or has already passed through the cluster, remains open.…”
Section: Merger Scenarios For the Ngc 4839mentioning
confidence: 99%